The effectiveness of 3D hologram as a new advertising medium in Klang Valley, Malaysia - Mohd Khairulnizam Ramlie; Mohd Khairul Azahari Abdul Rani; Mazia Udang; Ahmad Sofiyuddin Shuib (Penerbit Universiti Kebangsaan Malaysia, 2016)
Marketing communications is currently experiencing a period of major change. One of the biggest factors is a response from the current needs and high demands to replace the traditional media methods used. These changes have been impacted to the marketing communications. Since 1999 (Barnes, 1999) the ambient advertising has been applied and nowadays it has been improved based on current needs. From Andy Warhol (1963), when you see the ‘pop’ factor in the advertising, you will not see the sign in the same design. Statement in BBC news by Dr. Frank Shaw, he said that consumer will see a great step forward with 3D video ads, which react to their context and mood changes. It is clear from this report that we are at a critical point. In order to create visual 3D hologram as a most important research, the medium advertising is a first step to be used widely. In addition, this study is also focus on development of new medium for advertising using a hologram as an alternative medium for advertising as to expand the usage of holograms in Malaysia. The medium advertising told us that the impact from the research is the 3D hologram as a message delivery. Moreover, the experiment also helps to cut costs either than to make the observation, collecting data and analysis, to create 3D hologram. As a conclusion, findings from this analysis product test in public area will be further discussion for the advantages and disadvantages.